Time Budget and Activity Patterns During the Mating Period of Flat-headed Cat Prionailurus planiceps in Captivity - Danaisawadi, Patchara; Piriyarom, Sutida; Krasaeden, Warit; Pramkasem, Satreerat; Rurkkhum, Saranya; Yimprasert, Surasak (Tropical Natural History, 2023)
This study focused on the daily activity of flat-headed cats Prionailurus planiceps, which are currently recognized as endangered. Activity of one male and one female cat in captivity was observed from 8–15 June 2017 by using video cameras at the Department of Conservation and Animal Health Research, Songkhla Zoo, Songkla Province, Thailand. Observations were gathered on each individual by ad libitum sampling for 24 hours (daytime 06:00–18:00 and nighttime 18:00–06:00). The observed behaviors and time budget were recorded and used for constructing an ethogram. Finally, the daily activities were analyzed and compared between the male and female. The activity patterns of the cats could be classified into six categories: maintenance, feeding, rest, affiliation, aggression, and vigilance. The cats were commonly active at night and rested during the daytime. The male cat spent more time to rest during the day and was more active than the female at nighttime. Meanwhile, the female presented longer periods of affiliation behavior than the male during daytime and spent more time feeding than the male at night. In addition, the activity patterns of these flat-headed cats were similar to the natural activity of leopard cats P. bengalensis and other felids in the genera Felis and Leopardus.